Conformism, spontaneity and conscious direction - Cospito, Giuseppe (International Gramsci Journal, 2025)
Gramsci’s analyses and proposals on school and education should not be considered from a strictly pedagogical point of view but understood within the broader project of “intellectual and moral reform” that runs through the entire prison reflection passing through the “translation” of historical materialism into the “philosophy of praxis”. Therefore, a careful consideration of some key-concepts of this reflection is required. In formulating a conception that is aimed at overcoming any dichotomy between “state” and “civil society”, “public” and “private”, in order to arrive at a “regulated society” in which the “passage from the realm of necessity to the realm of freedom” preconized by the old Engels can be accomplished, Gramsci in fact reformulates with sometimes polemical audacity the meaning of terms such as “conformism”, “spontaneity”, “discipline” and “conscious direction”. In this way, he also rethinks the concept of “human nature”, which, as he could already read in the Third Thesis on Feuerbach, is defined only in a dialectical relationship between individual and environment, or, as Marx writes, between educator and educated. In order to reconstruct this conceptual galaxy, I will make use of the tools and methods of Gramscian philology developed by Gianni Francioni, trying to examine in a diachronic key the genesis, developments and interconnections of some of the Prison Notebooks fundamental categories, looking for their remote origin in the pre-prison political writings.